It-Mediated Customer Service Content and Delivery in Electronic Governments: An Empirical Investigation of the Antecedents of Service Quality1 - Tan, Chee-Wee; Benbasat, Izak; Cenfetelli, Ronald T. (MIS Quarterly, 2013)
Despite extensive deliberations in contemporary literature, the design of citizen-centric e-government websites remains an unresolved theoretical and pragmatic conundrum. Operationalizing e-government service quality to investigate and improve the design of e-government websites has been a much sought-after objective. Yet, there is a lack of actionable guidance on how to develop e-government websites that exhibit high levels of service quality. Drawing from marketing literature, we undertake a goal approach to this problem by delineating e-government service quality into aspects of IT-mediated service content and service delivery. Whereas service content describes the functions available on an e-government website that assist citizens in completing their transactional goals, service delivery defines the manner by which these functions are made accessible via the web interface as a delivery channel. We construct and empirically test a research model that depicts a comprehensive collection of web-enabled service content functions and delivery dimensions desirable by citizens. Empirical findings from an online survey of 647 respondents attest to the value of distinguishing between service content functions and delivery dimensions in designing e-government websites. Both service content and delivery are found to be significant contributors to achieving e-government service quality. These IT-mediated service content functions and delivery dimensions represent core areas of e-government website design where the application of technology makes a difference, especially when considered in tandem with the type of transactional activity. A split sample analysis of the data further demonstrates our model’s robustness when applied to e-government transactions of varying frequency.